(3OhQ efXheI GdahGJjQ hGdEjUGdGJ GdEdjcJQhfjI cEMOi BdjGJ GdJMhd GdQbej HeUdMI GdVQGFH aj QaY caGAI haYGdjI GdaMU GdVQjHj defTBJ GdCYeGd (B:s (3OQGSI ejOGfjI (B/s - (3,TjQjf eMeO CMeO SdjeGfs; (3YHO GdYRjR GdSjO eUWais; (3eMeO gTGe GdMehjs (2024)
(3JgOa gPg GdOQGSI Edi JMOjO eOj JCKjQ GdaGJhQI GdGdjcJQhfjI hGdGjUGd GdGdjcJQhfj Ydi caGAI haYGdjI GdaMU GdVQjHj GdGdcJQhfj dJMbjb GdgOa GdSGHb bGeJ GdHGMKI HELQGA OQGSI ejOGfjI hJeKd eLJeY GdOQGSI aj GdeJYGedjf aj eLGd GdJMGSH GdVQjHj HTCf eehdj GdVQjHI Ydj GdONd hGdecdajf HVQjHI GdbjeI GdeVGaI, hHdZJ YjfI GdOQGSI (B77 (3eaQOI, hbO Je JMdjd GdHjGfGJ hGNJHGQ aQhV GdOQGSI HGSJNOGe GdCSGdjH GdEMUGFjI GdhUajI hebjGS djcQJ GdNeGSj hCSdhH JMdjd GdJcQGQGJ hGdfSH GdeFhjI dgPg GdJcQGQGJ hJMhjd GdELGHGJ Gdj bje QbejI HGSJNOGe GdHQGeL GdEMUGFjI ddYdhe GdGLJeGYjI (BSPSS 27. (3JhUdJ fJGFL GdJMdjd GdEMUGFj ddOQGSI Gdj Gf GdGYJeGO Ydj GdaGJhQI hGdGjUGd GdGdjcJQhfj jDOj Gdj QaY eSJhj GdGeJKGd GdVQjHj hJbdjd GdJgQH GdVQjHj ceG Gfg jDOj Gdj SQYI hObI hYOGdI ELQGAGJ GdJMGSH GdVQjHj hQaY caGAI GdaMU GdVQjHj, hGf fXGej GdaGJhQI hGdGjUGd GdGdcJQhfj jbJVj GdJMhd Gdj CSdhH GdaMU GdVQjHj GdGdcJQhfj HeG jJfGSH eY GdHjFI GdeUQjI hjJhGab eY hGdeJWdHGJ GdJbfjI GdJj JJYdb HJWhjQ GdfXe GdGdcJQhfjI, ceG CXgQJ GdfJGFL bHhdG hGSkYG dYfGUQ GdfXGe GdGdcJQhfj GdebJQM ef bHd GdHGMKIs
This study aims to determine the extent of the impact of the electronic invoice and electronic receipt on the efficiency and effectiveness of electronic tax audit. To achieve the previous goal, the researcher conducted a field study and the study community represented in those who dealing in the field of tax accounting regarding income tax payers and value-added tax payers. The study sample amounted to 77 individuals. The data were analyzed and the study hypotheses were tested using descriptive statistical methods, the five-point Likert scale, the method of analyzing frequencies and percentages of these frequencies, and converting the answers into numerical values using the statistical programs for social sciences SPSS 27. The results of the statistical analysis of this study concluded that reliance on the electronic invoice and receipt leads to raising the level of tax compliance and reducing tax evasion. It also leads to the speed, accuracy and fairness of tax accounting procedures and raising the efficiency of tax auditing. The electronic invoice and receipt systems require a shift to the electronic tax audit method in a manner that is compatible with the Egyptian environment and is consistent with the technical requirements related to the development of electronic systems. The results also showed wide acceptance of the elements of the electronic system proposed by the researcher.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B126-132.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdVQGFHs -- (3eMGSHIs; (3GdJMhd GdQbej s -- (3GdGbJUGO GdQbejs -- (3GdGbJUGO GdQSej hGdZjQ QSejs